Analisis Genangan Banjir di Kawasan Sekitar Kolam Retensi dan Rencana Pengendaliannya, Studi Kasus: Kolam Retensi Siti Khadijah Palembang - Al Amin, M. Baitullah (Jurnal Perencanaan Wilayah dan Kota, 2016)
The area near the Siti Khadijah Palembang retention pond, especially Demang Lebar Daun street, is frequently inundated because of the overflowing of the retention pond, causing long traffic jams. This study aims to analyze the characteristics of flood inundation within the area for the existing situation and for a scenario of flood control using a pump system and an increase in open space. The flood routing within the retention pond was done using HEC-HMS software, while visualization of flood inundation was carried out using Global Mapper software. The results show that the capacity of the retention pond at this time is insufficient to accommodate run-off volume, whereas the flood peak discharge of 22.2 m3/s for a 5-year return period has the potential to inundate 11.09 Ha of the surrounding area. Flood control using pumps with a total capacity of 4 m3/s is able to reduce the inundation extent by 58.79%, while a 30% increase inÂ  open space is only able to reduce the inundation extent by 15.33%. Furthermore, a combination of flood pumps and an increase in open space can reduce the inundation extent by 75.92%. Using this method results in a maximum inundation depth of less than 0.5 m with a potential inundation time of only 20 minutes, where Demang Lebar Daun street is no longer inundated. For short-term flood mitigation, there is a need to build a flood pump station at the Siti Khadijah retention pond , while for long-term mitigation there is a need to gradually and sustainably provide open space.